The Cost of Doing Business in Africa : Evidence from Enterprise Survey Data - Eifert, Benn; Gelb, Alan; Ramachandran, Vijaya (2012)
Data from the World Bank Enterprise Surveys show that indirect costs (related to infrastructure and services) account for a relatively high share of firms' costs in poor African countries and pose a competitive burden on African firms. We estimate firm-level revenue and value-added functions for six industries in 17 developing countries, demonstrating that firm performance is sensitive to the cost of indirect inputs. As indirect inputs are not usually included in estimations of value added, we argue that existing estimates understate the relative performance of African manufacturing firms.